Real Time Fractional Robust Adaptive Scheme for Frequency Regulation in Double Area Hybrid Power System With Renewables - Ahmed Ragab; Dalia Allam; Ahmed F. Zobaa; Hazem Ali Attia (IEEE Access)
Load frequency regulation in hybrid grid is a very crucial issue. This work introduces robust-adaptive control methodology to provide accurate response against any disturbances. Control scheme of two main parts has been introduced. The first one is a novel fractional order model reference adaptive controller where fractional calculus merits and e-modification robust algorithm have been merged with the adaptive skills creating the fractional order model reference robust-adaptive controller. This robust-adaptive controller has utilized output feedback approach that requires only the output state without detailed system model information. The fractional orders have been optimized using a nature-inspired algorithm named Artificial Rabbits. The second part of the control scheme is a disturbance rejection observer that is able to estimate and eliminate external and internal disturbances. For fair comparison, results of the proposed scheme have been compared to that of the most efficient controllers obtained from the literature named fractional order proportional integral derivative controller and integral controller. Furthermore, the integer version of the proposed controller has been tested and compared with the proposed controller to prove the robustness of the fractional modification. To validate the superiority of the proposed controller, five challenging scenarios have been considered, encompassing load fluctuations, integration of renewable energy sources, changes in system parameters and time delay attacks. The proposed controller effectively minimizes area control error achieving stability and showing cost function enhancement of 15% to 152% compared to other tested controllers in all scenarios. Thus, it is strongly recommended for load frequency regulation in multi-area power systems.